(3cJGH GdJLQHI GdWHjIs - (3LGdjfhSs
(3ChdgG (B:s
(3bGd LGdjfhS Cbhd Cf UfGYI GdWH EfeG hLOJ hGSJNQLJ ai Chd GdbjGS eY GdJLGQH s
(3BNQgG (B:s
(3Cf LejY GdCSHGH GdJi jQGhG HgG CfeG GSJNQLJ HGdbjGS Ke Hjf HYO Pdc Gfg dG MGLI HfG Edjg ai gPG GdhbJ ai TF Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3YhQV HGdCUd Gdefbhd efgs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs